The Role of Digital Marketing in Improving Company Financial Performance - Yendra, Yendra (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study investigates the role of digital marketing strategies in enhancing a company's financial performance through a systematic literature review. It focuses on the impact of Search Engine Optimization (SEO), content marketing, and the integration of multiple digital marketing channels, as well as the influence of critical metrics like Customer Acquisition Cost (CAC), Return on Investment (ROI), and Customer Lifetime Value (CLV). The research employs a qualitative approach, analyzing peer-reviewed articles and relevant literature from the past decade sourced from databases such as Scopus, Web of Science, and Google Scholar. Thematic analysis was conducted to synthesize findings on the effectiveness of digital marketing strategies and metrics. Results indicate that SEO and content marketing significantly boost organic traffic and financial metrics, enhancing sales and customer retention. The integration of multiple digital channels amplifies these effects, improving overall ROI. Effective management of CAC, ROI, and CLV is crucial for financial optimization, with strategies focusing on personalized marketing and data-driven approaches showing the most success. External factors such as economic conditions and technological advancements moderate these effects. The study highlights the importance of adopting integrated digital marketing strategies and adapting to external changes and consumer behavior to sustain financial performance. Future research should explore industry-specific applications and the role of emerging technologies.